Assessing the quality of nursing clinical placement: A quantitative cross‐sectional study - Nadiah A. Baghdadi; Taghreed Alotaibi; Sally Mohammed Farghaly Abdelaliem (Nursing Open, 2023)
Abstract Aim To evaluate the quality of nursing clinical placement among nursing students. Design This is a descriptive cross‐sectional study. Methods Two hundred eighty two nursing student completed self‐administered, online questionnaires. The questionnaire assessed participants' socio‐demographic data, and the quality of their clinical placement. Results The students had a high mean score for the overall satisfaction of their clinical training placement with high mean score for the item of “patient safety was fundamental to the work of the units” and the item of “I anticipate being able to apply my learning from this placement,” while the lowest mean score was related to “This placement was a good learning environment” and “Staff were willing to work with students.” Patient or Public Contribution: Quality of clinical placement is critical for improving the everyday quality of care for patients who are in desperate need of caregivers with professional knowledge and skills.